MicroRNAs in neuronal development, function and dysfunction - Saba, Reuben; Schratt, Gerhard (Brain research, 2010)
Due to the complex architecture of the brain, the precise regulation of the numerous genes and signalling molecules involved is paramount. A recently identified class of master regulatory molecules, known as microRNAs (miRNAs), have the potential to assist in the countless regulatory mechanisms that occur in the brain during neuronal development and function. In the process, these molecules have gained the ability to provide a very pervasive and potent layer of genetic control. MiRNAs, in general, are genome encoded, short, non-protein coding RNA molecules that are involved in gene regulation by targeting for translational repression and/or degradation large numbers of mRNA molecules simultaneously. While the brain is replete with miRNAs, their particular role(s) in the developmental and functional programs of neurons is just emerging. Additionally, dysfunction of these molecules may also contribute to the etiology of several neurodegenerative conditions. Therefore, the central aim of this review is to highlight recent findings in the field of miRNAs in neuronal development, function and dysfunction.